2009
DOI: 10.1038/bmt.2009.248
|View full text |Cite
|
Sign up to set email alerts
|

Sequential intensified chemotherapy with stem cell rescue for children and adolescents with desmoplastic small round-cell tumor

Abstract: The RMS4.99 study was designed to explore the role of early sequential intensified chemotherapy (SICT) with PBSC rescue in patients with soft tissue sarcoma with a poor prognosis. Fourteen patients with desmoplastic small round-cell tumor (DSRCT) were included in this study. Initial chemotherapy was followed by a course of CY and etoposide with subsequent PBSC harvest, then three consecutive intensified chemotherapy combinations followed by PBSC rescue and G-CSF administration: first cycle thiotepa (150 mg/m(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 15 publications
1
17
0
2
Order By: Relevance
“…Bertuzzi et al reported on a cohort of 10 adult patients prospectively treated with high-dose melphalan plus mitoxantrone or thiotepa and found no improvements in overall survival [ 22 ]. Alternative approaches using sequential and multiple ASCTs administered earlier in the course of therapy were associated with equally poor outcomes [ 23 ]. Additional evidence of lack of effectiveness of ASCT was the poor response to the regimens used in our study with only a minor response noted in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Bertuzzi et al reported on a cohort of 10 adult patients prospectively treated with high-dose melphalan plus mitoxantrone or thiotepa and found no improvements in overall survival [ 22 ]. Alternative approaches using sequential and multiple ASCTs administered earlier in the course of therapy were associated with equally poor outcomes [ 23 ]. Additional evidence of lack of effectiveness of ASCT was the poor response to the regimens used in our study with only a minor response noted in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin is a common thread in the treatment of patients who either achieved long-term survival or had response to a standard consolidative radiotherapy dose of 30 Gy when delivered by external beam to the whole abdomen and pelvis [ 57 , 58 ]. Myeloablative chemotherapy with thiotepa and carboplatin, etoposide followed by autologous bone marrow, or peripheral stem cell rescue has been employed with limited success [ 56 , 61 ]. Case report of [ 90 Y]yttrium microspheres radioembolotherapy leading to a dramatic sustained reduction in the hepatic metastatic load has also been reported [ 59 , 62 ].…”
Section: Treatmentmentioning
confidence: 99%
“…For these advanced-stage patients, symptomatic treatment is more practical as it alleviates acute discomfort; however, it still leads to a poor outcome. Aggressive multimodality therapy with immunotherapy or bone marrow ablation and dose-intensive chemotherapy with autologous peripheral blood stem cell support may have potential benefit for DSRCTs and may be a promising new approach [8]. Recently, continuous hyperthermic peritoneal perfusion at the time of complete tumor resection has been developed as an adjunct to treat DSRCTs; this may prolong disease-free survival in selected cases [9].…”
Section: Discussionmentioning
confidence: 99%